Could the academic advisor, intrinsic motivation, and time management influence students’ attitudes towards research work on campus? - Miraj, Muhammad; Lu, Chuntian; Rehman, Ramiz ur; Osei-Bonsu, Robert; Mohd Said, Ridzwana; Ali, Rizwan; Shereen, Saima (IOS Press, 2022)
BACKGROUND:Research is essential and necessary for those who love learning, whether they belong to a research institution or not. Numerous elements influence researchers’ attitudes towards good research work, but in this study we focus on the most significant ones: advisor support, intrinsic motivation, timing, and planning. OBJECTIVES:The current study aims at motivating readers to help improve students’ attitudes towards research work within the university context. METHOD:The target demographic of the current research comprises masters and doctoral students from three major public institutions in Xi’an, China. We aimed to examine the effects of the variables and the study employed correlation and stepwise regression. RESULTS:The results show that advisor support influences attitudes towards research positively and significantly (β= 0.20, p < 0.01). Likewise, intrinsic motivation has a positive and significant effect on attitude towards research (β= 0.18, p < 0.01). Time attitudes significantly influenced attitudes towards research (β= 0.14, p < 0.05). Furthermore, time planning also positively and significantly influenced the attitude towards research (β= 0.15, p < 0.05). CONCLUSION:To achieve an excellent attitude towards research work, students need a cooperative academic advisor who will intrinsically motivate them in their research activities. However, they must manage their academic time and be equipped with time management skills.